Is Elective Interval Appendicectomy after Successful Initial Conservative Management of Appendicular Mass Necessary? - Noori, Ibrahim F. (AL-Kindy College Medical Journal, 2014)
Background The traditional management of appendicular mass is an initial conservative treatment followed by interval appendectomy. Recently interval appendicectomy has been questioned.Objective: The purpose of this study was to clarify the need and the role of interval appendicectomy after successful initial conservative treatment.Method: This is a prospective study conducted in a major hospital in Basra from April 2006 to Septemper2010, included 65 patients with appendicular mass which subsequently proved postinflammmatory (phlegmonous) changes of the appendix were treated conservatively.Results: Routine interval appendicectomy was not performed and needed after successful treatment in the majority of the patients (84.6%). Four patients (6.1%) developed abscess formation and operationwas necessary to drain the abscess. Four patients were readmitted with recurrent appendicitis after 2 months. During the 2 years follow up period another 2 patients presented with recurrent symptoms of acute appendicitis and appendectomy were arranged. The recurrence rate after successful conservative treatment was 10%.Conclusion routine interval appendectomy after initialsuccessful conservative treatment is of questionablebenefit and needs further assessment.